A Latent Profile Analysis of Violent Offenders Based on PCL-R Factor Scores: Criminogenic Needs and Recidivism Risk - Lehmann, Robert Johann Bernhard; Neumann, Craig S.; Hare, Robert Douglas; Biedermann, Jürgen; Dahle, Klaus-Peter; Mokros, Andreas (Frontiers in Psychiatry, 2019)
Clinicians and theorists have often proposed the two psychopathic subtypes of “primary” and “secondary” psychopathy, with recent research indicating some empirical support for both psychopathy subtypes, though the findings across studies are far from uniform. For the current study, latent profile analysis was used to investigate if homogeneous latent classes exist within a sample of 215 adult male violent offenders from Berlin, Germany. The age of the offenders at the time of the index offense ranged from 19 to 59 years. The results indicated a solution with four latent classes, which we refer to as prototypical psychopaths (LC1), callous-conning offenders (LC2), sociopathic or dyssocial offenders (LC3), and general offenders (LC4). Validation of the four subtypes involved examination of differences on recidivism risk; criminogenic needs; and general, violent, and sexual reoffending. The results also are discussed in terms of the issue of treatment amenability.